Transformation of Muhammadiyah's Da'wah in the Digital Era: Progressive-Digital Da'wah Model as an Innovation of the Progressive Islamic Movement - Rendi Marta Agung; Nuryuana Dwi Wulandari; Ratna Anjani; Harba Rahmanto Sari Tanjung (Bulletin of Indonesian Islamic Studies, 2025)
This study discusses the transformation of Muhammadiyah's da'wah from the pre-digital era to the digital era, by highlighting the development of the Progressive-Digital Da'wah model as an innovation in the progressive Islamic movement. Using the literature study method, this study found that digitalization is not just a change in da'wah media, but rather part of Muhammadiyah's ideological and epistemological strategy in responding to global social dynamics. This study employs documentation techniques to collect data from books, journal articles, official websites, and digital media related to Muhammadiyah's da'wah. The data were then analyzed using qualitative content analysis to identify patterns, themes, and meanings behind Muhammadiyah’s digital transformation strategies. The results of the study show that Muhammadiyah has succeeded in adapting da'wah through the use of digital platforms such as YouTube, podcasts, social media, and online learning systems (LMS), accompanied by an inclusive, collaborative, and participatory approach. Muhammadiyah's digital da'wah targets the millennial and Gen Z generations with popular language, attractive visuals, and tolerant and contextual narratives. In addition, a collaborative approach with NGOs, creative communities, and digital platforms strengthens the social impact of this da'wah movement. Muhammadiyah's Progressive-Digital Da'wah Model proves that progressive Islamic values can be effectively contextualized in the digital space to answer the challenges of the times and build an inclusive, civilized, and just civilization. This article contributes to the discourse on Islamic communication and da'wah by offering a model that integrates digital innovation with progressive Islamic principles in addressing contemporary societal challenges.